Car model reconstruction from images through character line recognition. Issue 5 (2nd August 2018) - Wang, Bo; Giannini, Franca; Monti, Marina; Li, BaoJun; Hu, Ping; Liang, JiCai
Abstract : Purpose: This paper aims to automatically derive a 2D parametric model of the main characteristic lines of a car from images, blueprints or hand-made sketches of its side view. Then this model can be used for the further computer-aided design manipulation starting from images of the side view of a car. Design/methodology/approach: The method combines different image edge detection techniques and edge removal processes with optimization techniques according to local and global constraints specific of the single curves to automatically construct a precise parametric model of the main character lines of a car from images. First, process the car image to compute the most important curves and then warp a car template model to match its feature points and curves with the ones detected in the image. Findings: The paper provides method to construct parametric model from an image using maximum cover ratio to the edge points obtained by state-of-the-art edge detection algorithms. A feature points' organization mechanism produces quadric curves to express feature curves of a product. Research limitations/implications: The robustness of the presented method depends on the completeness of edge detection results and the accuracy of some key points' registration result, so if the image is not good, the result cannot be trusted. Only side-view is considered in this paper. Additional limits in the process regard the side view verification: pictures of the front or rear view can be wrongly classified as lateral ones when they contain round lights. Practical implications: This program enables designers to convert the image to geometric parametric model directly. Originality/value: The method is applicable to shaded pictures, sketches and blue prints of the side view of a car. It can process a database of car images in a batch mode or a specific picture on user demand. The method classifies the cars to different categories: SUV/Wagon/Hatchback, sedan, city and coupe. The authors obtain good results for every category.